Relationship between Health Problem and Suicide Ideation among Correctional Officers - Razali Othman, Mohd; Abdullah, Suraida; Mohd Taib, Tasnim; Mazlina Ghazali, Nor; Fatihah Abdullah Bandar, Nur (International Journal of Psychosocial Rehabilitation, 2020)
This study investigated the relationship between health problems and suicidal ideation amongst 157 correctional officers from three institutions of prison in Malaysia. The participants completed an online assessment to identify their problems and rule out suicidal ideation. The existence and severity of health problems were assessed by using the Employee Needs Assessment Inventory (ENAI), while the Interpersonal Needs Questionnaire (INQ) evaluates the presence of suicidal ideation. Overall, health problems were found to be positively related to suicide ideation (r=.210**, p<0.05). Severity of health problems contributing to the feeling of thwarted belongingness and perceived burdensomeness measures it as a risk factor amongst personal problems addressed in ENAI. This research contributes to the exploration of health issues faced by correctional officers in Malaysia and how it affects their mental thoughts, which can guide the development of interventions to help them to better cope and reduce the possible development of suicide ideation.